Identifikasi Kemampuan Menulis Permulaaan Anak Usia 5-6 Tahun Di TK Negeri Pembina Kecamatan Sungai Penuh - Dora eliza; Khairani .; Norliza Milany; Silvia Wilandari; Masyunita Siregar, M.Pd (CV. ITTC INDONESIA, 2023)
Children's first writing skills can be developed from an early age. Therefore, the author states that there is a gap between expectations and reality in the Sungai Banyak Kindergarten, namely that children's initial writing abilities have not yet developed perfectly, while children who are one year old have not yet developed fully. The aim of this research is to measure the development of early writing skills in the age range of 5 to 6 years through clay games at the Sungai Banyak Kindergarten. It is hoped that this research will be useful as knowledge to improve children's early writing skills through playdough games. This research uses a qualitative approach using Classroom Activity Study research methodology. The research subjects were 6 female students in group B of the Sungai Banyak Kindergarten. The data collection technique used was participant observation. The data analysis used in this research is descriptive qauntitative. Data analysis that explains reality or facts based on the data obtained. Study results show that children aged 5 to 6 years can improve their initial writing skills by playing with playdough.